Mapificación de la fertilidad del suelo en la zona de Río Bonito empleando los sistemas de información geográfica - Tapia León, Paulo Wladimir (2012)
This research on the mapping of soil fertility in the Rio Bonito using geographic information systems and their objectives were: 1. The study of soil fertility on the farm Josue, 2. Generate maps of soil fertility and 3. Develop a fertilization program for growing cacao. The area used for the study was 20 ha, which took 23 soil samples which were sent to the laboratory. With the results of analyzes of soil fertility classes determined with the same appreciation very low, low, moderate, high and moderately high, it was used for the scoring table and appreciation of soil fertility Geographic Institute Agustín Codazzi. Using ArcGIS 10 software generated maps fertility, and for developing fertilization programs take into account the nutritional requirements of cocoa farming and fertility rates obtained. From the study it was determined that the soil of the farm consists of two classes Josue fertility, moderate and low, which were represented at a general map and also the pH, CIC, total bases, base saturation, organic carbon, nitrogen and total phosphorus. There were two fertilization programs for growing cocoa.